The editio princeps of Luigi Pirandello’s translation of Goethe’s Roman Elegies (Giusti, 1896): Pirandello and Ugo Fleres ‘translators’ and friends (Prassi Ecdotiche della Modernità Letteraria, 2021)
The article presents the editio princeps of Luigi Pirandello’s translation of Goethe’s Roman Elegies (Livorno, Giusti 1896), reconstructing how its publication was fraught with difficulties, highlighting the features of that edition as well as the role of Ugo Fleres as its illustrator and the way in which the illustrated edition was received by Pirandello’s contemporaries; lastly, it examines both Pirandello’s reflections in his essay Illustratori, attori e traduttori (1908) and the way in which he considered the job of illustrating a book as a “form of translation” and thus that Ugo Fleres’ contribution as an illustrator was not merely complementary.